건물 지붕, 건물 벽, 도로의 표면 거칠기 길이 증가가 도시 도로 협곡의 오염물질 분산에 미치는 영향: 큰 에디 모의 - 김동휘(Dong-Hwi Kim); 한범순(Beom-Soon Han); 박경주(Kyeongjoo Park); 홍성호(Seong-Ho Hong); 백종진(Jong-Jin Baik) (한국대기환경학회지(국문), 2024)
Understanding flow and pollutant dispersion in urban areas is important to well cope with urban air pollution. The roughness of urban surface influences urban flow and pollutant dispersion, which necessitates further understanding. This study examines how the increase in roughness length of each of building roofs, building walls, and roads affects flow and pollutant dispersion in urban street canyons using the PArallelized Large-eddy simulation Model (PALM). A simulation in which all the roughness lengths are 0.01 m and three additional simulations in which the roughness length of each of building roofs (ROOF), building walls (WALL), and roads (ROAD) is increased to 0.05 m are performed. The street canyonaveraged (pedestrian level-averaged) pollutant concentration is 0.8% (0.7%) lower (higher) in the ROOF simulation, 1.6% (12.5%) higher in the WALL simulation, and 9.6% (18.0%) higher in the ROAD simulation, than that in the control simulation of 12.5 μg m-3 (14.4 μg m-3). The magnitude of vertical mean pollutant flux within the street canyon is smaller in the ROOF, WALL, and ROAD simulations than in the control simulation. Compared with the control simulation, the upward vertical turbulent pollutant fluxes in the ROOF and WALL simulations are noticeably larger near the roof level and within the street canyon, respectively. Quadrant analysis at the roof level shows that the frequency of pollutant ejection (sweep) event in the ROOF simulation is 1.4%p (2.0%p) higher (lower) than that in the control simulation, while that in the WALL simulation is 0.9%p (1.6%p) lower (higher). These frequency changes largely occur in the central part of the street canyon rather than in the upwind and downwind parts. Meanwhile, the frequency of each turbulent event in the ROAD simulation is similar to that in the control simulation. This study gives further insights into the effects of increased roughness on pollutant dispersion. KCI Citation Count: 0